Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Klien Kantor Notaris dan PPAT Restu Mardhatillah - Nengsih, Novia; Novita, Era (Jurnal Manajemen Bisnis Syariah, 2025)
The purpose of this study was to analyze the effect of service quality and price on client satisfaction at the Notary Office and PPAT Restu Mardhatillah, S.H., M.Kn. This type of research is field research with a quantitative approach. The population in this study are all clients who have used the services of the Notary Office and PPAT Restu Mardhatillah, S.H., M.Kn in 2023 as many as 406 clients. The sample in this study amounted to 80 respondents whose number was determined using the slovin formula. Data collection techniques using questionnaires and documentation. Technical analysis using Multiple Linear Regression analysis. The results showed that partially the quality of service and price had a significant effect on client satisfaction at the Restu Mardhatillah Notary and PPAT Office, S.H., M.Kn. Furthermore, simultaneously service quality and price also have a significant effect on client satisfaction